Effect of Al~2~O~3~ Passivation on Structured Si/PEDOT:PSS Hybrid Solar Cell - Sameer Alghanmi; Khalid Alshammari (Yanbu Journal of Engineering and Science)
Recently, silicon/organic heterojunction solar cells (HSCs) attain great attention because of its attractive characteristics such as rationally high efficiency, low cost, and simple device fabrication technique. However, inferior junction conformity between structured Si and PEDOT: PSS still remains a great challenge. Here, a superior, conformal, and uniform Al~2~O~3~ thin layer is deposited on structured pyramid n-Si wafer to enhance the front junction conformity using atomic layer deposition (ALD) technique. The deposited Al~2~O~3~ thin layer provides better wettability of PEDOT:PSS compared to native oxide, which minimizes pores, and pin-hole density usually occurs in spin-coating process. Additionally, Al~2~O~3~ thin layer acts as an electron-blocking and hole-transporting layer, resulting in an effective charge separation as well as transport, which boosts the power conversion efficiency. The interface-modified device demonstrates a high open-circuit voltage of 0.612 V as well as a fill factor of 70.7%, leading to a stable efficiency of 14.3% for structural n-Si/PEDOT: PSS HSCs.